Understanding community health needs and forging an academic global health partnership in Puebla, Mexico: a mixed methods study. Issue 1 (April 2020) - Remmert, Veronica; Ciaburri, Christina; Sandoval, Andrea; Stephenson, Claire; Rojas, Alfonso; Hernandez, Eder; Hernandez, Luis; Ward, Peter; Ainslie, Ricardo; Mercer, Tim
Abstract: Background: Academic global health partnerships can help address population health needs, particularly in low-resource settings. To be effective, they must start with a detailed understanding of community health needs, and involve the voice of the community. In Puebla, Mexico, a team from the Benemerita Universidad Autonoma de Puebla (BUAP) and the University of Texas at Austin (UT), undertook a comprehensive community health needs assessment of four low-income communities. Methods: An interdisciplinary team was formed from staff and students at UT and BUAP, along with local community organisers from the Fundacion Communitaria de Puebla (FCP) in Mexico. We selected one urban community and three rural agrarian communities from the region surrounding the town of Atlixco in Puebla, Mexico. We designed a comprehensive health needs assessment with the following objectives: to understand the perceptions and priorities of the health needs of families; to characterise health behaviours, risk factors, resource use patterns, and access issues; and to describe the intersection between the built environment and health through an exploration of housing, water, and air quality. To achieve these objectives, we implemented a comprehensive, pragmatic, and responsive mixed-methods approach including semi-quantitative household surveys, key informant qualitative interviews, focus group discussions, intensive case studies of dwelling units, and technical air and water quality sampling of each household surveyed. Findings: We included data from 242 household surveys, four key-informant interviews, six focus group discussions, and five case studies of dwelling units collected between June 3 and July 26, 2019. Mean household size was four people and mean focus group discussion size was ten participants. We noted common, and unique, issues and patterns emerging across each community. These included misinformation on the causes and treatment of diabetes; mental health trauma after the 2017 Puebla earthquake; housing conditions, agricultural practices, and indoor air pollution that jeopardise the health of families; and socioeconomic barriers affecting access to care, particularly in the rural agrarian communities. Furthermore, this project helped forge the working relationships between UT, BUAP, FCP, local community leaders, and the Ministry of Health in developing an academic global health partnership that can further explore and respond to these findings. Interpretation: Engagement with communities to develop a deep understanding of their needs and priorities is of great importance. Addressing these needs will require a combination of further research, education, clinical care, public health interventions, and new policy proposals. This community health-needs assessment galvanised the start of an academic global health partnership between UT and BUAP that will adapt the Academic Model Providing Access to Healthcare (AMPATH) paradigm to work with communities and public-sector health-care delivery systems to improve population health outcomes. Funding: The President's Award for Global Learning, The University of Texas at Austin